2019
DOI: 10.3390/ijerph16244956
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Cardioprotective Assumptions for National Drinking Guidelines and Alcohol Harm Monitoring Systems

Abstract: The existence and potential level of cardioprotection from alcohol use is contested in alcohol studies. Assumptions regarding the risk relationship between alcohol use and ischaemic heart disease (IHD) are critical when providing advice for national drinking guidelines and for designing alcohol harm monitoring systems. We use three meta-analyses regarding alcohol use and IHD risk to investigate how varying assumptions lead to differential estimates of alcohol-attributable (AA) deaths and weighted relative risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…However, few studies have employed these methods, with covariate-adjusted, conventional cohort analyses remaining dominant, preventing a conclusive picture of the nature of these relationships from emerging. Given that associations found between moderate alcohol consumption and good health impact safe drinking guidelines and public health policy (51,52), further research employing methods to mitigate confounding and other biases is urgently required to establish whether such findings are truly causal.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have employed these methods, with covariate-adjusted, conventional cohort analyses remaining dominant, preventing a conclusive picture of the nature of these relationships from emerging. Given that associations found between moderate alcohol consumption and good health impact safe drinking guidelines and public health policy (51,52), further research employing methods to mitigate confounding and other biases is urgently required to establish whether such findings are truly causal.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the authors stated that health benefits from moderate drinking should no longer play a role in decision making. Furthermore, Sherk et al [ 65 ] suggested a need of downward revisions to daily consumption levels, which would result in safe drinking with no added risks. On the contrary, many authors, such as Sacks et al [ 66 ], have considered the positive effects of drinking.…”
Section: Discussionmentioning
confidence: 99%
“…This will be a novel perspective through which to examine the literature on whether moderate alcohol consumption is protective, focusing on those studies that best promote causal inference from observational research. The presumption that the associations found between moderate alcohol consumption and good health reflect a causal relationship significantly impacts burden of disease estimates, safe drinking guidelines and public health policy [44,45]. The importance of the proposed review will therefore lie in helping to establish whether such findings are truly causal.…”
Section: Discussionmentioning
confidence: 99%